Towards a Holistic Definition of Model‐Based System Engineering: Paradigm, Modeling and Requirements. Issue 1 (October 2015) - Aboutaleb, Hycham; Monsuez, Bruno
Abstract: Current systems complexity has reached a degree that requires addressing conception and design issues while taking into account all the necessary aspects. Therefore, one of the main challenges is the way complex system models are specified and designed. The exponential growing effort, cost, and time investment during the phase of modeling a complex systems emphasize the need for a paradigm, a framework, and an environment to handle the system model complexity. For that, it is necessary to understand the expectations of the human user of the model and his limits. This paper presents a generic framework for designing complex systems, highlights the requirements a system model needs to fulfill to meet human user expectations, and defines the refined functional as well as non‐functional requirements that modeling tools needs to meet to be useful in model‐based system engineering.